Penentuan Kriteria Perbuatan Permulaan Pelaksanaan Pada Tindak Pidana Makar di Indonesia - Wahyu Andrie Septyo; Erdianto Effendi; Evi Deliana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Makar comes from the word aanslag (Dutch), which according to the literal meaning is an attack or attack. P. A. F. Lamintang has another interpretation of makar or aanslag which means attack or attack with no good intention. While makar according to Article 87 of the Criminal Code: "It is said that there is a plan to do an act, if the intention for it has turned out from the beginning of implementation, as referred to in article 53". So article 87 of the Penal Code only gives an interpretation of the term "makar" and does not give its definition. With article 87 of the Criminal Code, the plan to do such an act if there is an intention for it has existed, which turns out from the initial act of implementation as referred to by article 53 of the Criminal Code. Makar during the Old Order was more concrete because it pointed to real events while during the Reformation, the article makar has been applied even though no real action has occurred. The existence of early acts such as raising the flag, attending meetings has been considered a perfect act. Contrary to a number of facts of recent debates, it shows evidence that the constitutional court ruling that considers the debate on makar has not resolved the issue. Moreover, the Decision of the Constitutional Court does not make interpretations or create new norms about the meaning of makar. This needs to be a determination of the criteria for the initial act of criminal treason in Indonesia. The formulation of problems in this research is First, How is the implementation of cases of the initial implementation of criminal acts in Indonesia? Second, What is the ideal formulation for determining the criteria for the initial implementation of makar crimes in Indonesia?The research method used is a type of normative legal research or literature law research. Research is conducted on legal principles and legal comparisons related to the problems examined. This research was obtained by studying and reviewing books, legislation, various scientific works, and others. Data analysis in this research was conducted qualitatively.The results of the study that law enforcement against the initial implementation of criminal acts during the old order is more concrete than the reform period that reaped many pros and cons and multi-interpretation in its application. The initial act of implementation of the makar crime in Indonesia still refers to the colonial regulation (Criminal Code) related to the elements of the makar crime. It is necessary to formulation new norms in the determination of the initial actions of this implementation through the fulfillment of several criteria of such actions such as meeting the criteria of organized, systematic, massive and serious as the basis for consideration of law enforcement officers conducting law enforcement.Keywords: Makar, Criteria, Beginning of Implementation.